Family Cohesion and Entrepreneurial Orientation for Family Business Longevity - Arifin Djakasaputra; Ronnie Resdianto Masman; Sarwo Edy Handoyo; Hadi Cahyadi; Juliana Juliana (Penerbit Goodwood, 2026)
Purpose: This study examines the influence of family cohesion and entrepreneurial orientation on family business longevity through the mediating roles of family harmony and innovation capability. It addresses the limited integration of socio-emotional and entrepreneurial perspectives in explaining the sustainability of family businesses. Research Methodology: A quantitative approach was employed using survey data from 255 Indonesian family business owners and managers. Data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) to test the proposed relationships. Results: The findings revealed that family cohesion significantly enhanced family harmony, and entrepreneurial orientation positively influenced innovation capability. Family harmony and innovation capability have significant positive effects on family business longevity. Mediation analysis confirmed that family harmony and innovation capability mediated the relationships between family cohesion and family business longevity and between entrepreneurial orientation and family business longevity, respectively. Conclusions: Family business longevity is shaped by both socioemotional and entrepreneurial dimensions, with family harmony and innovation capability serving as key mechanisms supporting intergenerational continuity. Limitations: The cross-sectional design and Indonesian context may limit the generalizability of these findings. Contributions: This study integrates socio-emotional wealth and entrepreneurial perspectives into a unified framework of family business longevity and provides practical insights into strengthening family harmony, innovation, and long-term business sustainability across generations.